Effect of endometrial scratch injury on pregnancy rate after previously failed intrauterine insemination - Keskar, Jagruti Ratnakar; Prabhu, Santoshi Ramkrishna; Savani, Gayatri Vishal; Mishra, Nigamananda; Jadhav, Vaishali Rohan; Bhenki, Deepak Subhash (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Endometrial receptivity plays an important role in implantation and successful pregnancy. In literature, various attempts have been made to improve endometrial receptivity. Endometrial scratch injury (ESI) is one such intervention widely offered to improve endometrial receptivity in women with a history of in-vitro-fertilization (IVF) failure. In our present study, this procedure of ESI was performed in cases with previously failed intrauterine insemination (IUI) and its effect on pregnancy rate was assessed. Methods: A prospective, randomised, controlled study was conducted at Fertility Clinic, Bhabha Atomic Research Centre Hospital, Mumbai. Total 200 women requiring IUI with previously failed one IUI were included in the study. They were randomly divided into 2 groups of 100 each. Both the groups underwent controlled ovarian stimulation with clomiphene citrate and gonadotropins followed by IUI. Study group underwent “endometrial scratching” in mid-proliferative phase of the same cycle preceding IUI. Control group underwent IUI alone. Pregnancy rates (clinical and ongoing) were compared in both the groups. Results: Endometrial scratching group had significantly higher (<0.0002) (8.4±2.3 mm versus 7.3±1.9 mm) endometrial thickness at the time of ovulation trigger. Clinical pregnancy rate was significantly higher (p<0.0001) (42% versus 16%) in endometrial scratching group with no significant difference in ectopic pregnancy, miscarriage and multiple pregnancy rates in both the groups. Conclusions: Due to its role in improving pregnancy rates in women with previously failed IUI, clinicians should offer ESI in mid-proliferative phase of the same cycle preceding IUI, before offering advanced IVF treatment.